2019
DOI: 10.1016/j.jbusres.2018.08.037
|View full text |Cite
|
Sign up to set email alerts
|

Terrorism and country-level global business failure

Abstract: This paper contributes to the literature on business failure by investigating the relationship between terrorism and country-level global business failure by using a sample of 174 countries over the period 2009-2015. To proxy for business failure, the 'Resolving Insolvency' index, which is a component of the World Bank's 'Doing Business' index, was adapted and used. The results of the fixed-effects estimation show that terrorism has a positive and significant relationship with business failure for the full sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 84 publications
2
29
0
Order By: Relevance
“…Many empirical studies seek to establish the impact of terrorism on business performance (e.g., Abadie & Gardeazabal, 2008;Aslam & Kang, 2015;Chen & Siems, 2004;Chesney et al, 2011;Drakos, 2004Drakos, , 2010Graham & Ramiah, 2012;Ito & Lee, 2005;Procasky & Ujah, 2016;Tingbani, Okafor, Tauringana, & Zalata, 2019). The collective evidence suggests a significant relationship between terrorism and business performance.…”
Section: Empirical Evidence On Terrorism and Business Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Many empirical studies seek to establish the impact of terrorism on business performance (e.g., Abadie & Gardeazabal, 2008;Aslam & Kang, 2015;Chen & Siems, 2004;Chesney et al, 2011;Drakos, 2004Drakos, , 2010Graham & Ramiah, 2012;Ito & Lee, 2005;Procasky & Ujah, 2016;Tingbani, Okafor, Tauringana, & Zalata, 2019). The collective evidence suggests a significant relationship between terrorism and business performance.…”
Section: Empirical Evidence On Terrorism and Business Performancementioning
confidence: 99%
“…Specifically, they found that Spain and the UK are generally less affected by terror shocks, which suggested that financial investors in these two countries are more resilient to these events. Very recently, Tingbani et al (2019) investigated the impact of terrorism on global business failure. Evidence from their fixed-effects estimations reveals a significantly negative relationship between terrorism and business failure.…”
Section: Empirical Evidence On Terrorism and Business Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The causes and consequences of business failure are the two dominant streams ( Shepherd, 2013 ; Khelil, 2016 ). As studies addressing the causes have increased ( Artinger and Powell, 2015 ; Tingbani et al, 2019 ), numerous research initiatives have probed the consequences ( Singh et al, 2015 ; Amankwah-Amoah and Wang, 2019 ). Studies on the consequences have found simultaneously negative and positive outcomes ( McGrath, 1999 ; Ucbasaran et al, 2013 ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Despite many years of war and violence between multiple political and religious factions (Barakat and Zyck, ), we have limited understanding about the business environment of Afghanistan (Bullough, Renko, & Myatt, ; Dearing, ; Kwong, Cheung, Manzoor, & Rashid, ; Schutte, ). It is well known that constant war and conflict have many harmful impacts on economic activities within the country(De Clercq, Haq, & Azeem, ; Tingbani, Okafor, Tauringana, & Zalata, ), such as increasing operating expenses (Giunipero & Aly Eltantawy, ), reducing the returns on investment (Meierrieks and Gries, ), diminishing individual intentions to engage in entrepreneurial activities (Bullough et al, ), damaging the financial stability of businesses (Kitchen, ), and exacerbating the risk of losing one's entire capital, not to mention one's life (Holmén, Min, & Saarelainen, ), which lead eventually to creating poverty on an endemic scale (Kwong et al, ). Expanding on this literature for the first time, our study provides empirical evidence of the harmful effects of perceived danger on employees' well‐being at the workplace.…”
Section: Introductionmentioning
confidence: 99%